Analysis of total aflatoxins in commercially available cereal products in the Republic of North Macedonia - Dimovska, Elena; Zhivikj, Zoran; Gavazova, Elizabeta; Petreska ivanovska, Tanja; Petrushevska tozi, Lidija (Macedonian Pharmaceutical Association, 2023)
Aflatoxins, as naturally occurring toxins, can accumulate in maturing crops or in grain during transportation and represent serious threat for contamination of cereal processed products. Consumption of aflatoxin contaminated foodstuffs can cause acute or chronic toxicity in humans. With an aim to protect public health, maximum residue levels (MRLs) for these toxins are defined by the regulation authorities. To control the compliance of aflatoxin residues in cereal-based products to legislation, a convenient analytical technique that will provide rapid, specific, accurate and costly effective analysis such as ELISA method is required. In this study, concentration of total aflatoxins in twelve cereal processed products supplied under random selection from several retail outlets in Republic of North Macedonia was determined using commercially available RIDASCREEN Aflatoxin total kit. Analyses have shown that none of the examined samples contained aflatoxins above the MRLs (4 μg/kg). According to the obtained results, the ELISA method can be used for routine detection and quantification of total aflatoxins in cereal products due to simplicity, specificity and sensitivity. In addition, this study may initiate the use of immunochemical methods for analysis of potential aflatoxin contamination in order to establish data collection for the presence of these concerning toxins in cereal-based products available on the national market. Keywords: aflatoxins, ELISA, immunochemical, cereals